Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.18502/jfrh.v14i3.4670
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of Doing Intra-uterine Insemination 36 and 42 Hours after Human Chorionic Gonadotropin (HCG) Injection on Pregnancy Rate: A Randomized Clinical Trial

Abstract: Objective: Intrauterine insemination (IUI) is an assisted conception technique that involves the deposition of a processed semen sample in the upper uterine cavity, overcoming natural barriers to sperm ascent in the female reproductive tract. Hence, we compared the results of doing intra-uterine insemination 36 and 42 hours after human chorionic gonadotropin (hCG) hormone injection to achieve clinical and chemical pregnancy rates. Materials and methods: One hundred and sixty infertile women with unexplai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Concerning the oocyte, the ovulation time and its interval to IUI have been studied previously. Although there is still no consensus on the optimal time interval between hCG injection or LH surge and insemination, this interval can be influential on IUI outcomes ( Firouz et al , 2020 ). Several RCTs studying a long versus a short interval between hCG injection and insemination have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the oocyte, the ovulation time and its interval to IUI have been studied previously. Although there is still no consensus on the optimal time interval between hCG injection or LH surge and insemination, this interval can be influential on IUI outcomes ( Firouz et al , 2020 ). Several RCTs studying a long versus a short interval between hCG injection and insemination have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Several RCTs studying a long versus a short interval between hCG injection and insemination have been published. Analyzing different short (insemination at the point of hCG and 24 h after hCG) and long (insemination 36 h after hCG and 48 h after hCG) intervals, some of these studies have found comparable pregnancy results between the long and short groups ( Rahman et al , 2011 ; Rijsdijk et al , 2019 ), while others have found better pregnancy outcomes in the long group ( Firouz et al , 2020 ). However, little information is presented about the work-up methods of the semen and/or the time between semen processing and insemination in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of COH is to obtain as many good quality oocytes as possible (2). The ideal stimulation regimen for IVF should have minimal side effects, the lowest cycle cancellation rates, the least drug cost, easy monitoring, and single pregnancy should be achieved ultimately (3). Ovarian reserve should be clearly evaluated in every woman in whom IVF is planned.…”
Section: Introductionmentioning
confidence: 99%